Corrosion characteristics and damage constitutive model of galvanized steel wires for bridge cables. (December 2021) - Li, Rou; Miao, Changqing; Zhang, Yili; Wang, Yichun; Chen, Xianliang
Abstract: The characteristic parameters of corrosion pits on the surface of steel wires in service bridges are discussed. The degradation of mechanical properties of corroded steel wires and its relationship with different corrosion evaluation parameters are studied through tensile test. Finally, the damage constitutive model of corroded steel wires is established by introducing the damage variable D . The results show that there are four types of corrosion pits on the surface of steel wires, including the deep ellipsoid, shallow ellipsoid, groove and saddle shape. The higher the corrosion degree of steel wires, the less the number of deep ellipsoidal pits, the more the number of groove and saddle pits. The average corrosion depth of steel wires is positively correlated with the maximum pit depth, width and length. The strength of corroded steel wires mainly depends on the maximum pit depth. In addition, compared with the new steel wire, the average yield strength and ultimate strength of old steel wires decrease due to the influence of corrosion and the discreteness increases. The similarity of probability density function of new and old steel wires is high, and the corrosion has little effect on the elastic modulus of steel wires. Finally, the model curve is in good agreement with the experimental curve, and the proposed damage model of corroded steel wires is basically accurate.